CRF transcription factors in the trade-off between abiotic stress response and plant developmental processes - Gentile, Davide; Serino, Giovanna; Frugis, Giovanna (Frontiers in Genetics, 2024)
Climate change-induced environmental stress significantly affects crop yield and quality. In response to environmental stressors, plants employ defence mechanisms and growth suppression, creating a resource trade-off between the stress response and development. Although stress-responsive genes have been widely engineered to enhance crop stress tolerance, there is still limited understanding of the interplay between stress signalling and plant growth, a research topic that can provide promising targets for crop genetic improvement. This review focuses on Cytokinin Response Factors (CRFs) transcription factor's role in the balance between abiotic stress adaptation and sustained growth. CRFs, known for their involvement in cytokinin signalling and abiotic stress responses, emerge as potential targets for delaying senescence and mitigating yield penalties under abiotic stress conditions. Understanding the molecular mechanisms regulated by CRFs paves the way for decoupling stress responses from growth inhibition, thus allowing the development of crops that can adapt to abiotic stress without compromising development. This review highlights the importance of unravelling CRF-mediated pathways to address the growing need for resilient crops in the face of evolving climatic conditions.